2021
DOI: 10.13057/biodiv/d220803
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Diversity of sponges associated in seagrass meadows at coastal area of Pacitan District, East Java, Indonesia

Abstract: Abstract. Setiawan E, Chodiantoro MR, Insany GF, Subagio IB, Dewi NK, Muzaki FK. 2021. Short Communication: Diversity of sponges associated in seagrass meadows at coastal area of Pacitan District, East Java, Indonesia. Biodiversitas 22: 3105-3112. Sponges are sessile organisms and aquatic filter feeders that play an important role in marine ecosystems. They are also secondary metabolite compounds that exhibit promising novel properties. Indonesia has been categorized as a hot spot for sponge diversity. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…We found 10 sponge species in our studied seagrass meadow, similar to other studies. For example, 9–11 sponge species were reported inhabiting seagrass meadows in East Java – Indonesia (Setiawan et al ., 2021). One to 10 sponge species were also found in sub-temperate seagrass meadows on the south-eastern Australia coast (Demers et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 10 sponge species in our studied seagrass meadow, similar to other studies. For example, 9–11 sponge species were reported inhabiting seagrass meadows in East Java – Indonesia (Setiawan et al ., 2021). One to 10 sponge species were also found in sub-temperate seagrass meadows on the south-eastern Australia coast (Demers et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Ismet et al (2017) reported 18 sponge species inhabiting a multispecies seagrass meadow in the Seribu Islands National Park, Jakarta, which had species-specific correlations with each seagrass species cover in the meadow. Meanwhile, 16 sponge species were recorded in two seagrass meadows in the Gulf of Pacitan, East Java, where the assemblages were dominated by the boring sponge Spheciospongia inconstans (Setiawan et al, 2021). There are still major gaps in our knowledge of the ecology of sponge assemblages in seagrass ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Ismet et al (2017) reported that a total of 18 sponge species inhabited a multispecies seagrass meadow in the Seribu Islands National Park, Jakarta, which had a species-specific level of correlation with each seagrass species' cover in the meadow. Meanwhile, 16 sponge species were recorded in two seagrass meadows in the Gulf of Pacitan, East Java, where the assemblages were dominated by the boring sponge Spheciospongia inconstans (Setiawan et al 2021). There are still major gaps in our knowledge on the ecology of sponge assemblages in the seagrass ecosystems, especially in this important biogeographic region.…”
Section: Mckenziementioning
confidence: 99%
“…I found ten sponge species in my studied seagrass meadow, similar to other studies. For example, 9 to 11 sponge species were reported inhabiting seagrass meadows in East Java -Indonesia (Setiawan et al 2021). One to ten sponge species were also found in sub-temperate seagrass meadows on the southeastern Australia coast (Demers et al 2015).…”
Section: Sponge Species Richness and Abundancementioning
confidence: 99%